2014
DOI: 10.1128/jvi.03202-13
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible Protein IFI35 Negatively Regulates RIG-I Antiviral Signaling and Supports Vesicular Stomatitis Virus Replication

Abstract: In a genome-wide small interfering RNA (siRNA) screen, we recently identified the interferon (IFN)-inducible protein 35 (IFI35; also known as IFP35) as a factor required for vesicular stomatitis virus (VSV) infection. Studies reported here were conducted to further understand the role and requirement of IFI35 in VSV infection. Consistent with the siRNA screening data, we found that depletion of IFI35 led to reduced VSV replication at the level of viral gene expression. Although no direct interaction of IFI35 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 58 publications
(76 reference statements)
4
73
1
Order By: Relevance
“…Protein kinase C-α/β (PKC-α/β) phosphorylates RIG-I and blocks RIG-I-mediated induction of type I IFN27. The IFN-inducible protein IFI35 suppresses dephosphorylation and activation of RIG-I and mediates degradation of RIG-I via K48-linked ubiquitination, resulting in blockage of type I IFN induction28.…”
mentioning
confidence: 99%
“…Protein kinase C-α/β (PKC-α/β) phosphorylates RIG-I and blocks RIG-I-mediated induction of type I IFN27. The IFN-inducible protein IFI35 suppresses dephosphorylation and activation of RIG-I and mediates degradation of RIG-I via K48-linked ubiquitination, resulting in blockage of type I IFN induction28.…”
mentioning
confidence: 99%
“…Sendai virus [13]. Although the reasons for this discrepancy are not known, the contradicting results may be due to the differences in cell type (primary normal human MCs versus immortalized cell line HEK293) or experimental conditions (addition of authentic doublestranded RNA poly IC versus infection with Sendai virus).…”
Section: Imaizumi Et Al: Ifi35 and Tlr3 Signaling Pathways In Hman Mcsmentioning
confidence: 61%
“…IFI35 molecule has a leucine zipper domain in its structure and is thought to regulate the gene expression, although it lacks the DNA-binding motifs [12]. It was recently reported that IFI35 negatively regulates antiviral signaling of RIG-I in HEK293 cells infected with Sendai virus [13]. Furthermore, IFI35 expression has been reported in fibroblasts, macrophages, epithelial cells and HeLa cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitin ligase RNF125 has been described to add K48-linked polyubiquitin on RIG-I to promote its degradation and downregulate the signaling [118]. The interferon-induced protein IFI35 was found to associate with RIG-I and not only promote its degradation but also prevent dephosphorylation by PP1 [119]. Premature degradation of RIG-I can compromise antimicrobial signaling.…”
Section: Regulating the Function Of Rig-i In Cellsmentioning
confidence: 98%